Integration of Traditional Ecological Knowledge in Problem-Solving Model: Its Impact on Students' Learning Outcomes and Environmental Awareness - Zulyetti, Diana; Salsa Billa Ramadhani; Opi Rahmah Hidayat; Nurleila Sitepu; Elijonnahdi (Biology and Education Journal, 2026)
Students’ low academic achievement and limited environmental awareness suggest that biology instruction has not yet fully supported the development of both conceptual understanding and environmental responsibility. In many cases, learning also remains disconnected from students’ local contexts, particularly from Traditional Ecological Knowledge(TEK), which can make scientific concepts feel less meaningful and relevant to their everyday lives. Addressing this gap requires learning approaches that are both contextual and engaging. Therefore, this study aims to examine the impact of integrating TEK into the Problem Solving model on students’ learning outcomes and environmental awareness. This study employed a quasi-experimental method with a post-test only control group design. The sample consisted of two groups of 10th-grade students at SMA Negeri 4 Payakumbuh, namely an experimental class and a control class. The instruments used included a learning outcome test and an environmental awareness questionnaire, both of which had been validated. Data were analyzed using independent sample t-tests and descriptive analysis. The results showed that students in the experimental class achieved higher average learning outcomes (83.69) compared to those in the control class (78.57), with a statistically significant difference at the 0.05 level (t-calculated = 2.45 > t-table = 1.67). In terms of environmental awareness, students in the experimental class also demonstrated higher scores, particularly in the knowledge aspect (81.80 vs. 73.37) and critical awareness (73.85 vs. 67.24). However, improvements in the attitude and behavior aspects were relatively modest. These findings suggest that integrating TEK into the Problem Solving model can effectively enhance students’ cognitive outcomes and their critical awareness of environmental issues. Nevertheless, fostering changes in environmental attitudes and behaviors may require more sustained and long-term educational interventions.